The Health Economics of the spinal cord injury or disease among veterans of war: A systematic review. (2nd November 2017) - Furlan, Julio C.; Gulasingam, Sivakumar; Craven, B. Catharine
Abstract : Context: Information on health-care utilization and the economic burden of disease are essential to understanding service demands, service accessibility, and practice patterns. This information may also be used to enhance the quality of care through altered resource allocation. Thus, a systematic review of literature on the economic impact of caring for SCI/D veterans would be of great value. Objective: To systematically review and critically appraise the literature on the economics of the management of veterans with SCI/D. Methods: Medline, EMBASE and PsycINFO databases were searched for articles on economic impact of management of SCI/D veterans, published from 1946 to September/2016. The STROBE statement was used to determine publication quality. Results: The search identified 1, 573 publications of which 13 articles fulfilled the inclusion/exclusion criteria with 12 articles focused on costs of management of SCI/D veterans; and, one cost-effectiveness analysis. Overall, the health care costs for the management of SCI/D veterans are substantial ($30, 770 to $62, 563 in 2016 USD per year) and, generally, greater than the costs of caring for patients with other chronic diseases. The most significant determinants of the higher total health-care costs are cervical level injury, complete injury, time period ( i.e. first year post-injury and end-of-life year), and presence of pressure ulcers. Conclusions: There is growing evidence for the economic burden of SCI/D and its determinants among veterans, whereas there is a paucity of comparative studies on interventions including cost-effectiveness analyses. Further investigations are needed to fulfill significant knowledge gaps on the economics of caring for veterans with SCI/D.